Reactive power sharing based on proportional-resonant controller - Jie, Huamin (Nanyang Technological University, 2020)
Microgrid is widely used as a feasible, efficient and stable structure to integrate distributed energy resources (DERs) based on their interacting converters. For economic and safety reasons, these converters are expected to operate automatically in complex situations to enhance system reliability and reduce attention from operators. Conventionally, the droop-control can realize automatic distribution of reactive power of DERs’ inverters by linking power to their corresponding frequency and voltage magnitude. In general, the active power sharing accuracy of P-f droop control is relatively high within a certain margin of error, while simplest Q-V droop control often deteriorates due to different value of their line impedances. Therefore, a new Q-V ̇ droop control method is proposed to take the place of traditional fashion to improve the accuracy of the reactive power sharing as well as the quality of entire block. In addition, as a companion component, proportional-integral (PI) controller is an effective mean way to achieve closed-loop control and output control signals with pulse-width-modulation (PWM). However, the PI controller cannot achieve the astatic control of the sine or cosine quantity. Therefore, the vector control systems of rectifiers need to use coordinate transformation technology to convert sinusoidal quantities such as current and voltage in a three-phase stationary coordinate system into DC quantities in a synchronous rotating coordinate system. In short, conversion from abc coordination system to dq0 coordination system is required. On the contrary, the process can be governed by proportional-resonant (PR) control, which reduces the coordinate transformation loop and simplify the system. In addition, this PR controller changes current and voltage from abc coordination system to αβ coordination system, so the coupling relationship between the current in d and q axis can be eliminated. In this project, the Q-V ̇ droop control method with a modified V ̇ restoration technique is applied with PR controller. Its operation principle and effect on the power sharing is specifically analyzed. Simulation tests based on MATLAB are conducted to validate the effectiveness of proposed model.